5n+32=-6(3-5n)

Simple and best practice solution for 5n+32=-6(3-5n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5n+32=-6(3-5n) equation:



5n+32=-6(3-5n)
We move all terms to the left:
5n+32-(-6(3-5n))=0
We add all the numbers together, and all the variables
5n-(-6(-5n+3))+32=0
We calculate terms in parentheses: -(-6(-5n+3)), so:
-6(-5n+3)
We multiply parentheses
30n-18
Back to the equation:
-(30n-18)
We get rid of parentheses
5n-30n+18+32=0
We add all the numbers together, and all the variables
-25n+50=0
We move all terms containing n to the left, all other terms to the right
-25n=-50
n=-50/-25
n=+2

See similar equations:

| -23-(-38)=x=6 | | 3(1-8a)=195 | | 2w-6=5+3w-3 | | 5x+4x-14=28-5x | | 11.3z+19.24=8.6z–19.92+12.97 | | t^2–14t–15=0 | | k+6/26=1 | | x2=58(x−4) | | w+68=-40 | | 80=10(3+x) | | x/2=5/8(x-4) | | 3(1+3n)+4=61 | | -23-(-38)=x/6 | | -3=-4+m/8 | | 6/x-10=2 | | 8x=-1/12-5/6 | | -8(4+r)=-144 | | g^2–12g+20=0 | | m-4/9=257/90 | | m-13=-10 | | 3(6k-1)=69 | | 5/4=x/2-1/6 | | 2.4z+6.3=-1.7z+47.1 | | -15=k/7 | | x-(-53/5)=41/2 | | 4x+6-10=3x-2 | | 0.2(100+x)=30+0.10 | | 0.6b+0.43=0.9b+0.7 | | 70=1/2x(6+1) | | 20+a=11 | | 0.6b=0.43=0.9b+0.7 | | -6=x/19 |

Equations solver categories